Transient Ischemic Attacks Preceding Ischemic Stroke and the Possible Preconditioning of the Human Brain: A Systematic Review and Meta-Analysis - Ghozy, Sherief; Kacimi, Salah Eddine Oussama; Elfil, Mohamed; Sobeeh, Mohamed Gomaa; Reda, Abdullah; Kallmes, Kevin M.; Rabinstein, Alejandro A.; Holmes, David R.; Brinjikji, Waleed; Kadirvel, Ramanathan; Kallmes, David F. (Frontiers in Neurology, 2021)
Stroke is one of the leading causes of mortality and disability worldwide. Transient ischemic attack (TIA) is transient brain ischemia with temporary neurological deficits. In animal models, prior TIA seems to enhance brain ischemic tolerance to withstand further ischemic events which can be explained by brain preconditioning. Thus, the aim of this review is to formulate evidence of whether TIAs can induce positive preconditioning and enhance the functional outcomes in patients suffering from subsequent ischemic strokes. Five databases were searched (PubMed, Embase, SAGE, Web of Science, and Scopus) and twelve studies were included in the quantitative analysis. Studies were eligible when comparing patients with acute ischemic stroke and previous TIA to those with acute ischemic stroke without TIA. Stroke severity represented by NIH severity scale (NIHSS), clinical outcomes including (length of hospital stay, mortality rate, and systolic and diastolic blood pressure), TOAST classification, and modified Rankin score (mRS). Odds ratio and mean difference and 95% confidence interval were used to describe our results using the random effect model. Our results revealed that patients with stroke and prior TIAs tend to have lower NIHSS scores on admission as compared to those without prior TIAs. However, the NIHSS score was not significantly different between the two groups at 7 days. Furthermore, there was no statistically significant difference between the two groups in terms of mortality. Despite the absence of differences in the admission mRS score between the two groups, patients with prior TIAs had lower mRS scores at discharge.